2017
DOI: 10.1080/13102818.2017.1335177
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses on medium optimization usingone-factor-at-a-time, response surface methodology, and artificial neural network for lysine–methionine biosynthesis byPediococcus pentosaceusRF-1

Abstract: Optimization strategy that encompassed one-factor-at-a-time (OFAT), response surface methodology (RSM), and artificial neural network method was implemented during medium formulation with specific aim for lysine-methionine biosynthesis employing a newly isolated strain of Pediococcus pentosaceus RF-1. OFAT technique was used in the preliminary screening of factors (molasses, nitrogen sources, fish meal, glutamic acid and initial medium pH) before proceeded to optimization study. Implementation of central compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 24 publications
(36 reference statements)
3
41
0
Order By: Relevance
“…Lactic acid bacteria (LAB) appear as an exceptional candidate owing to their non-pathogenic nature and reputation as Generally Recognized as Safe (GRAS) microorganism [9]. Moreover, numerous studies have reported that LAB possess capability to produce various amino acids [10–18]. Nevertheless, there were limited documentation on the application of LAB for amino acid production.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) appear as an exceptional candidate owing to their non-pathogenic nature and reputation as Generally Recognized as Safe (GRAS) microorganism [9]. Moreover, numerous studies have reported that LAB possess capability to produce various amino acids [10–18]. Nevertheless, there were limited documentation on the application of LAB for amino acid production.…”
Section: Introductionmentioning
confidence: 99%
“…The OFAT methodology allows studying one variable at a time, and implementing its optimal conditions to the analyses of the subsequent variables [14]. The OFAT methodology to study the growth parameters of L. crescens is evaluated using four criteria: pH optimization, aeration, temperature preference, and buffer requirements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the optimal growth conditions of L. crescens are presented for four growth parameters—pH, aeration, temperature and buffering capacity—using one factor at a time methodology (OFAT) [14]. The evaluation of the growth parameters of L. crescens gave insight into the physiology, lifestyle and culturability of the Ca.…”
Section: Introductionmentioning
confidence: 99%
“…This approach requires less number of experiments, equipments, and financials. In addition, the data obtained from this approach is much more reliable, understandable, can be used for prediction and simulation, and allow for evaluation of the interactions among variables (Singh et al 2011;Nor et al 2017).…”
Section: Optimization Of the Factors Affecting Fungal Chitin And Chitmentioning
confidence: 99%